A multifunctional mesoporous silica–gold nanocluster hybrid platform for selective breast cancer cell detection using a catalytic amplification-based colorimetric assay. Issue 6 (29th January 2019) - Li, Mingqiang; Lao, Yeh-Hsing; Mintz, Rachel L.; Chen, Zhuanggui; Shao, Dan; Hu, Hanze; Wang, Hong-Xia; Tao, Yu; Leong, Kam W.
Abstract : Breast cancer detection : The biosensor based on HER2 antibodies attached to MSN–AuNC hybrids is sensitive, selective, economical and simple to operate. Abstract : Breast cancer is the most common malignancy and also the second leading cause of cancer mortality in women globally. Strategies for early and precise detection of breast cancer cells are highly desired in breast cancer diagnosis and treatment. Here, we report on the efficient detection of HER2-positive (HER2 + ) breast cancer cells using an amplified signal scheme enabled by gold nanoclusters entrapped in mesoporous silica nanoparticles (MSNs). The utilization of MSNs as an excellent enzyme immobilization support and gold nanoclusters as an effective peroxidase mimic imparts high sensitivity to this detection platform. In addition, the inclusion of target-specific HER2 antibodies adds excellent selectivity. Determination of HER2 + cancer cells in breast cancer tissue demonstrates the potential application of this biosensor design in clinical diagnosis in particular, and bioanalysis in general.